Expanding the chemical space of human serine racemase inhibitors. Issue 19 (1st October 2015) - Dellafiora, Luca; Marchetti, Marialaura; Spyrakis, Francesca; Orlandi, Valentina; Campanini, Barbara; Cruciani, Gabriele; Cozzini, Pietro; Mozzarelli, Andrea
Graphical abstract: Abstract: Serine racemase, the enzyme responsible ford -serine synthesis in the central nervous system, has been identified as a potential therapeutic target to treat N -methyl-d -aspartate receptors-related pathologies. The search for specific inhibitors of the enzyme has revealed that serine racemase is a difficult target, with the best inhibitor currently identified, 2, 2-dichloromalonate, showing a K i of 19 μM. In order to expand the chemical space of hit compounds, we have performed an in silico structure-based screening campaign on a filtered ZINC library applying the FLAP software. The identified hits were docked with GOLD and re-scored with HINT, and the most promising molecules experimentally evaluated on recombinant human serine racemase. Two inhibitors, with chemical structures totally unrelated to inhibitors described so far showed K i values of about 1.5 mM.